2011
DOI: 10.1111/j.1469-0691.2010.03448.x
|View full text |Cite
|
Sign up to set email alerts
|

Anidulafungin for the treatment of invasive candidiasis

Abstract: Candidaemia/invasive candidiasis (C/IC) is the most frequently occurring invasive fungal infection worldwide, with a particularly strong impact and high incidence in the intensive-care unit, where there is a need for new treatment options and strategies. The echinocandin anidulafungin has broad in vitro activity against a wide range of Candida species, along with favourable pharmacokinetics that allow administration in hepatic and renal impairment and with any comedication without the need for dose adjustments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 81 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…Also noteworthy is that anidulafungin was just as effective against C. parapsilosis as against other species. This particular pathogen has somewhat higher echinocandin minimum inhibitory concentrations (MICs) than other Candida species, although the clinical significance of these findings is unknown [9,26,27]. The treatment response for C. tropicalis was lower than for other Candida species and also lower than reported previously with anidulafungin for C. tropicalis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Also noteworthy is that anidulafungin was just as effective against C. parapsilosis as against other species. This particular pathogen has somewhat higher echinocandin minimum inhibitory concentrations (MICs) than other Candida species, although the clinical significance of these findings is unknown [9,26,27]. The treatment response for C. tropicalis was lower than for other Candida species and also lower than reported previously with anidulafungin for C. tropicalis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies and In vitro data demonstrate that anidulafungin is active against C. albicans and C. parapsilosis biofilms [ 47 ], and exhibits post‐antifungal effect (PAFE) (i.e. ongoing antifungal activity at limited exposure to an antifungal) like other members of echinocandins class [ 48 ]. An in vitro study reported that anidulafungin possesses PAFE for a longer period even at concentrations below its minimum inhibitory concentration (MIC) compared with fluconazole, caspofungin and amphotericin B, and in contrast, fluconazole has no PAFE effect at any of its concentration, caspofungin has a shorter PAFE period (0-2 h) and amphotericin B also exhibits a shorter duration of PAFE at levels below the MIC [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative FDG-PET/CT follow up is already performed in oncologic diseases such as lymphoma and melanoma to monitor treatment response, but may also be beneficial in patients with chronic infection and long-term antimicrobial treatment [ 78 ]. Additionally, (follow up) PET/CT may also aid physicians in deciding to switch from intravenous to oral antibiotic treatment, or from more expensive antifungals such as anidulafungin to the cheaper but maybe less effective fluconazole [ 79 ].…”
Section: Future Applications Of Pet/ctmentioning
confidence: 99%